Estimating thermal insulation performance and weather resistance of acrylonitrile-styrene-acrylate modified with high solar reflective pigments: Pr3+/Cr3+ doped BaTiO3. (1st September 2021) - Tian, Mengmeng; Chen, Chenlu; Han, Aijun; Ye, Mingquan; Chen, Xin
Graphical abstract: Highlights: The pigments having faint yellow and high near-infrared reflectance of 66.89–96.39% have been manufactured. ASA resin modified with synthetic pigments has higher solar reflectance of 58.85–81.68% compared with common ASA plastic. Internal surface temperature difference of ASA under NIR light irradiation reaches more than 6.4 °C. Modified ASA samples provide saving up to 18% of heat compared to unmodified ASA resin. Modified ASA samples have good weather resistance and prolonged service life. Abstract: This paper is conducted to evaluate the thermal insulation potential and weather resistance of modified acrylonitrile-styrene-acrylate (ASA) resin as building materials. The synthesized Pr 3+ /Cr 3+ doped BaTiO3 pigments were served as additives. The Ba1- x Pr x TiO3 ( x = 0.03, 0.04, 0.05) and Ba1- x Pr x Ti1- y Cr y O3 ( x / y = 0.03/0.03, 0.03/0.05, 0.05/0.05) pigments are the tetragonal replacement solid solution. The sample particles display approximately spherical and the powders all have a yellow tone. Ba1- x Pr x TiO3 and Ba1- x Pr x Ti1- y Cr y O3 pigments both exhibit distinctly high NIR solar reflectance of 94.39%-96.39% and 66.89%-91.50%, respectively. The variations of the NIR solar reflectance values are mainly attributed to the difference in free charge carrier concentration in the doped pigments. The NIR solar reflectance of ASA modified with 10 wt% pigments can reach 58.85%-81.68%. After performing near-infrared radiation, the inner surface temperature of the modified ASA can be reduced by 6.4 °C at a maximum than that of unmodified ASA, and the modified ASA provides saving up to 18% of heat. Moreover, the addition of NIR reflectance pigments can further improve the weather resistance of ASA materials. In short, the modified ASA can be effectively applied to building materials to maximize the heat-insulating effect and service life.